(untitled) (SCHOOLAR: Social and Literature Study in Education, 2024)
The background of this research is the educators of the fiqh subject do not carry out the process of reviewing the material or reviewing the material that has been submitted, have not used strategies, methods and active learning models that can increase student activity and increase student interest in learning so that it affects their learning outcomes. This research aims to determine the learning outcomes of the class X students of the Integrated MA Al Munawaroh Jombang using cooperative learning strategies of the Index Card Match type in class X students. This research is an experimental research with a Pre-Experimental design type One â€“ Group Pretest â€“ Posttest Design using one experimental class.Â The population in this research were all students of class X consist of 35 male students. Data collection techniques used is observation and tests. The data analysis technique used is descriptive analysis technique. The results showed that the learning outcomes of class X MA Integrated Islamic Senior High School Al Munawaroh using cooperative learning of the Index Card Match type in Qurban and aqiqah material experienced an increase marked by an average pretest score of 75.49 and the final post test score increased to 87.89. So that there is an increase in the average value of 12.40